Satisfaction of beneficiaries with community-based health insurance and associated factors in Legambo District, North-East Ethiopia: a cross-sectional study - Getaneh, Melaknesh Minda; Bayked, Ewunetie Mekashaw; Workneh, Birhanu Demeke; Kahissay, Mesfin Haile (Frontiers in Public Health, 2023)
Background The fundamental concept of community-based health insurance is to strengthen the healthcare financing system to access universal healthcare by reducing costly risk-coping strategies. The scheme’s sustainability and the quality of services provided by it are highly dependent on the satisfaction of its beneficiaries. Despite beneficiaries’ satisfaction being the key determinant for providing evidence for policy revision and decision-making, it has often been neglected. Therefore, the study investigated the community-based health insurance beneficiaries’ satisfaction and associated factors in Legambo district, North-East Ethiopia. Methods The study was conducted in the Legambo district with a community-based cross-sectional study design from October to November 2019. The data were collected from 838 households that had been the beneficiaries of the scheme using multi-stage and systematic random sampling. Twelve trained data collectors were employed and gathered the data using a pre-tested, structured questionnaire. We ran descriptive, bivariate, and logistic regression analyses. A value of p less than 0.05 with a 95% CI was used in multivariate logistic regression to determine the association of variables with the beneficiaries’ satisfaction. Results The overall satisfaction level of the beneficiaries of the scheme was 58.6% and was associated with the following factors: merchandize (AOR = 1.92, 95% CI = 1.02–3.63), living in rural areas (AOR = 1.52, 95% CI = 1.02–2.27), an early office opening time (AOR = 3.81, 95% CI = 2.04–7.10), a short time interval to use benefit packages (AOR = 4.85, 95% CI = 2.08–11.31), an inexpensive membership premium (AOR =10.58, 95% CI = 3.56–31.44), availability of laboratory services (AOR =2.95, 95% CI = 1.71–5.09), presence of referral services (AOR =1.93, 95% CI = 1.33–2.80), having immediate care at health facilities (AOR = 1.73, 95% CI = 1.01–2.97) and non-compulsory enrolment (AOR = 6.31, 95% CI = 1.64–24.20). Conclusion The beneficiaries’ satisfaction with the scheme was suboptimal and found to be determined by occupation, residence, laboratory and referral services, immediate care, office opening time, time interval to use benefit packages, premium amount, and situation of enrollment, most of which are service-related variables. Thus, to improve the satisfaction level, the stakeholders that should work hard seem to be the health insurance agency (the insurer) and the health facilities (the provider or supplier).